Binding Energies for CO on Clean and Oxygen-Modified Mo(110) Surface - Petrova, N.V. (Хімія, фізика та технологія поверхні, 2010)
The interaction of CO molecules with clean and oxygen-modified Mo(110) surface has been investigated by means of density functional (DFT) calculations. It has been found that on both clean and oxygencovered Mo(110) surfaces CO molecules are tilted with respect to the normal to the surface and adsorbed near hollow sites. The presence of oxygen substantially reduces the binding energy of CO molecule with the Mo(110) surface and on oxygen-saturated surface the adsorption of CO occurs completely blocked. The presence of the preadsorbed oxygen atoms on the Mo(110) surface results in the appearance of the 19 eV peak in local densities of states. The peak position corresponds to the chemical shift of the 2s oxygen line with regard to the electron states pertinent to oxygen atom in CO molecule. В рамках теорії функціонала електронної густини досліджено взаємодію молекули СО з чистою та модифікованою киснем поверхнею Мо(110). Показано, що як на чистій, так і на вкритій киснем поверхні Мо(110) молекула СО адсорбується під кутом до нормалі до поверхні і займає положення поблизу осей симетрії третього порядку. Наявність кисню на поверхні істотно зменшує енергію зв'язку молекули СО з поверхнею Мо(110), а насичення поверхні киснем призводить до повного блокування адсорбції молекул СО. Наявність кисню на поверхні Мо(110) обумовлює появу піку -19 еВ в спектрі густини станів. Положення цього піку відповідає хімічному зсуву 2s лінії кисню в порівнянні з електронними станами, притаманними атому кисню в адсорбованій молекулі СО. В рамках теории функционала электронной плотности исследовано взаимодействие молекулы СО с чистой и модифицированной кислородом поверхностью Мо(110). Показано, что как на чистой, так и на покрытой кислородом поверхности Мо(110) молекула СО адсорбируется под углом к нормали к поверхности и занимает положение вблизи осей симметрии третьего порядка. Наличие кислорода на поверхности существенно уменьшает энергию связи молекулы СО с поверхностью Мо(110), а насыщение поверхности кислородом приводит к полной блокировке адсорбции молекул СО. Наличие кислорода на поверхности Мо(110) приводит к появлению пика -19 эВ в спектре плотности состояний. Положение этого пика соответствует химическому сдвигу 2s линии кислорода по сравнению с электронными состояниями, характерными для атома кислорода в адсорбированной молекуле СО.